1996
DOI: 10.1111/j.1476-5381.1996.tb15766.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II receptors involved in the enhancement of noradrenergic transmission in the caudal artery of the spontaneously hypertensive rat

Abstract: 1 The effects of the AT, receptor antagonist losartan and the AT2 receptor antagonist PD 123319, on actions of angiotensin II in isolated caudal arteries of spontaneously hypertensive (SH) and age-matched normotensive (Wistar-Kyoto) rats were compared.2 Angiotensin II (0.1-3 gM) produced concentration-dependent increases in perfusion pressure in artery preparations from both SH and Wistar-Kyoto (WKY) rats, the maximal increase in the SH rat being significantly greater than the increase in WKY rats. The increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Whilst the mechanism of the interaction remains obscure, it would appear to warrant further study. This is reinforced by our subsequent observations with caudal artery preparations from spontaneously hypertensive rats of a similar synergistic interaction between PD 123319, rather than losartan, and the relatively low concentration of angiotensin II (0.1 gM) (Cox et al, 1996).…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…Whilst the mechanism of the interaction remains obscure, it would appear to warrant further study. This is reinforced by our subsequent observations with caudal artery preparations from spontaneously hypertensive rats of a similar synergistic interaction between PD 123319, rather than losartan, and the relatively low concentration of angiotensin II (0.1 gM) (Cox et al, 1996).…”
mentioning
confidence: 62%
“…Recently, we reported preliminary findings which indicated that angiotensin II exerted an action on transmitter noradrenaline release in the rat caudal artery which apparently opposed the well-known prejunctional facilitatory effect of the peptide (Cox et al, 1995b). Specifically, a low concentration of the AT,-selective antagonist losartan (0.01 4uM), was found to increase markedly the ability of angiotensin II to enhance the field stimulation-evoked efflux of [3H]-noradrenaline which had been incorporated into the noradrenergic transmitter stores of the artery.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite these pharmacological differences, both AT 1 antagonists are equally effective in inhibiting Ang-II-induced stimulation of catecholamine release, thus providing no further evidence for a different receptor subtype at vascular and neuronal sites. Subtypes of the AT 1 receptor, named AT 1A and AT 1B , exist in the rat [11], but they cannot be discriminated by losartan [11,37]. To date, there is only one report about HR 720 in the literature [17] which provides no information as to the AT 1 subtype specificity or a noncompetitive type of antagonism of HR 720.…”
Section: Discussionmentioning
confidence: 95%